Avaliação do balanço nitrogenado e aparecimento de nitrogênio uréico como marcadores de catabolismo, infecção e mortalidade em pacientes com lesão renal aguda em diálise - Bufarah, Marina Nogueira Berbel [UNESP] (2014)
Introduction: Hypercatabolism is the most important nutritional alteration in patients with acute kidney injury (AKI). Nitrogen balance (NB) and ureic nitrogen appearance (UNA) are measures that allow to estimate the extent of catabolism in AKI. Objectives: To describe and classify the catabolism of AKI patients on hemodialysis (HD) and high volume peritoneal dialysis (HVPD) and to examine whether NB and UNA are early markers of infection and mortality in these patients. Methodology: Prospective cohort study that evaluated AKI patients requiring dialysis at the Clinical Hospital of Botucatu Medicine College, from March 2011 to December 2012. The protocol study was performed using clinical and nutritional datas and parameters of catabolism. (such as reduction of at least 2g/day in NB or increased 2g/day in UNA) and assessment of presence of infection (fever, leukocytes above 12.000/mm ³ or CRP> 10mg/dl). All patients were followed by the medical staff since admission on unit nephrology until partial or complete recovery of renal function or death. This study was approved by the Ethics Committee of Research. Results are expressed as median or mean and standard deviation. To compare the clinical, nutritional and catabolism characteristics, t test, Mann-Whitney or chi-square were used. To investigate the association of NB and UNA with mortality and infection, t test or Mann-Whitney test and Kaplan-Meyer were used, respectively. The statistical significance level was p <0.05. Results: 124 patients were included, 96 in HD and 28 in HVPD. Patients had a median age of 63 years, prevalence of admission in ICU of 85.5%, AKI Severity Index (ATN-ISS) of 64.85% and mortality rate of 56.5%. HD and HVPD patients showed severe catabolism with NB median of -8.74 gN/day (-14.74;3.93 gN/day) vs. -7.36 gN/day (-13.46;-1.56 gN/day), p=0,73)], respectively. Measures of UNA were [16.74 gN/day (10.38 – 22.76 gN/day) vs. 12.97 gN/day (10.53 – 17.14), ...